Prevalence, Risk Factors and Prognosis of Cerebrovascular Accident and its Subtypes Among Admitted Patients in University of Science and Technology Hospital Sana'a, Yemen, 2022-2023 - Sa'adan, Amr Shuaib; Muharram, Mohammed Abbas; Ahmed, Salah Yahya; Dhemesh, Ammar Mohammed; Ali, Daifallah Taher (My University, 2023)
Background: stroke is the second leading cause of death and a major cause of disability worldwide and its late burden has mainly been attributable to developing countries. Yemen is one of these countries where epidemiological studies on stroke burden are scarce but necessary. Objective: This study aims to establish the prevalence, risk factors, and prognosis of cerebrovascular accidents and its subtypes among admitted patients at the University of Science and Technology Hospital Sana'a, Yemen.